Listening to Extinction: Early Conservation Radio Sounds and the Silences of Species. Issue 4 (4th January 2022) - Hui, Alexandra
Abstract: In the first decades of the twentieth century, American radio producers used both artificial and wild-recorded sounds of nature to promote principles of environmental conservation and wildlife management. These techniques were shaped by established listening practices — especially those of birders — and also fostered new ones. Specifically, conservation radio programs like those produced by the American Wildlife Institute and the Cornell Lab of Ornithology, made it possible for listeners to experience silence in a new way; as indicative of absence, potentially even extinction, both locally and globally. By examining how conservation radio in the 1930s was a mechanism through which environmental awareness and even action was fostered, this article demonstrates the dividends of working at the intersection of sensory studies and environmental history. New inflection points and temporal framing are made apparent as is the development of the critical sensory perceptual shifts necessary for the environmental movement to come. Tracing the sounds and listening to them in individuals' understanding of nature prompts us to consider the shifting, culturally-bound, mechanisms through which we have sensed and perceived and acted upon the world.